Psychometric properties for the alternative quality assurance evaluation model (QAEM) leadership characteristics of leaders (LCL) for national universities commission (NUC) accreditation instruments of the federal republic of Nigeria - Bolaji, Bojuwon Yusuf; Mohd Ali, Hairuddin (2013)
This research characterizes the first psychometric evaluation criteria for the alternative LCL QAEM constructs of NUC accreditation instruments to gauge the quality assurance evaluation of university educational institutions in Nigerian, comprising five factors: innovation, communication, motivation, pacifier and implementer. This research using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) on the 1600 sample data from 16 universities in the study area. Consequently, enhanced quality assurance approaches based on this research have been advocated for LCL to improve the effectiveness and efficiency of quality management by university administrators that the alternative QAEM construct of NUC indicated that the five (5)- factor measurement’s model with a factor of leadership characteristics of leaders (LCL) which comprised twenty-nine (29) instruments instead of the initially conceptualized measurement of 5- factor model, which comprised thirty-three (33).